Treatment Under the Spotlight and Kanguru Mother Care for Body Temperature among Premature Newborn - Pole, Jasper Suinite (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to find out how the comparison between kangaroo cares methods and treatments under the spotlight to control the body temperature of premature infants in the perinatology room port moresby general hospital, papua new guinea. This type of research is an experiment with a posttest only control design. The results obtained Mann-Whitney value of 0.589, which means the value of p-value> rather than Î± (0.05). Conclusion, there was no significant difference between the control group (under the spotlight treatment) and the intervention group (kangaroo maintenance method). Keywords: Kangaroo Mother Care, Premature newborn, Spotlights